2021
DOI: 10.3390/brainsci11050617
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and Proactive Adaptation of Cognitive and Motor Neural Signals during Performance of a Stop-Change Task

Abstract: The ability to inhibit or suppress unwanted or inappropriate actions, is an essential component of executive function and cognitive health. The immense selective pressure placed on maintaining inhibitory control processes is exemplified by the relatively small number of instances in which these systems completely fail in the average person’s daily life. Although mistakes and errors do inevitably occur, inhibitory control systems not only ensure that this number is low, but have also adapted behavioral strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 163 publications
(268 reference statements)
0
3
0
Order By: Relevance
“…Thus, behavioral differences and specific brain activity alterations could potentially be used as a biomarker of schizophrenia diathesis. Finally, in a very detailed and rich review, Brockett and Roesch [24] described the role of the rat brain regions in reactive and proactive inhibitory control. Although the authors mainly focused on single-unit and lesion data collected in their laboratory, they constantly draw parallels with data obtained in non-human primates and humans.…”
mentioning
confidence: 99%
“…Thus, behavioral differences and specific brain activity alterations could potentially be used as a biomarker of schizophrenia diathesis. Finally, in a very detailed and rich review, Brockett and Roesch [24] described the role of the rat brain regions in reactive and proactive inhibitory control. Although the authors mainly focused on single-unit and lesion data collected in their laboratory, they constantly draw parallels with data obtained in non-human primates and humans.…”
mentioning
confidence: 99%
“…Stimuli of either appetitive or aversive valence can drive attention in a way that subsequently facilitates decision-making and learning. We have found that attention-related signals in ACC can be driven by unsigned prediction errors when there are unexpected changes in outcome valence or cues that signal the need to change behavior ( Bryden et al, 2011 , 2019 ; Brockett et al, 2020 ; Brockett and Roesch, 2021 ).…”
Section: Anterior Cingulate Cortex’s Contribution To Reward Cognitive...mentioning
confidence: 96%
“…When it comes to adaptive motor control, most studies have focused on proactive or reactive inhibitory control 29 . Proactive control is when adjustments in the motor command are foreseen ahead of time, while reactive control is when the motor command must be adjusted in the moment 30 .…”
Section: Introductionmentioning
confidence: 99%